Promoting Open Science through bibliometrics: a practical guide to build an open access monitor - Bracco, Laetitia (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2022)
In order to assess the progress of Open Science in France, the French Ministry of Higher Education, Research and Innovation published the French Open Science Monitor in 2019. Even if this tool has a bias, for only the publications with a DOI can be considered, thus promoting article-dominant research communities, its indicators are trustworthy and reliable. The University of Lorraine was the very first institution to reuse the National Monitor in order to create a new version at the scale of one university in 2020. Since its release, the Lorraine Open Science Monitor has been reused by many other institutions. In 2022, the French Open Science Monitor further evolved, enabling new insights on open science. The Lorraine Open Science Monitor has also evolved since it began. This paper details how the initial code for the Lorraine Open Science Monitor was developed and disseminated. It then outlines plans for development in the next few years.